BETWEEN ACQUISITION AND LEARNING: ADULT SECOND LANGUAGE ACQUISITION PROCESS - Muhammad Saifuddin (Educate, 2014)
Muhammad Saifuddin Unipdu – Jombang saifuddin.unipdu@gmail.com Abstract Language acquistion and learning posit the way children get their second language. It defines the process of getting the language in which they may develop it in different circumstance. In the early ages, they acquire their second language in which it can be done through children - mother‟s communication or even through their social communication. Later, they tend to learn the second language. On the other hand, as they grow older and become adult, they conciously learn language. However, it is not always assumed that adult get their second language through learning but it is rather acquiring. Adult have more time exposure to a language acquisition that it shows their acquisition process is bigger than children‟s. The input also determines the acquirers to stimulate the language production where it refers to language competence and language performance in which both of them are also the principle of language acquisition. Keywords: Acquisition, Learning, Language Process Abstrak Proses pemerolehan dan belajar bahasa mengandaikan cara anak-anak mendapatkan bahasa kedua mereka. Artikel ini mendefinisikan proses pemerolehan bahasa di mana mereka mengembangkannya dalam situasi-situasi yang berbeda. Pada usia dini, mereka memperoleh bahasa kedua mereka melalui komunikasi ibu - anak atau bahkan melalui komunikasi sosial mereka. Kemudian, mereka cenderung untuk belajar bahasa kedua. Di sisi lain, saat mereka tumbuh dewasa dan menjadi dewasa, mereka dengan sadar belajar bahasa. Namun, itu tidak bisa diasumsikan bahwa orang dewasa mendapatkan bahasa kedua mereka selalu melalui pembelajaran tetapi sebenarnya mereka hanya sekedar mengakuisisi. Orang dewasa memiliki waktu akuisisi bahasa yang lebih banyak sehingga menunjukkan proses akuisisi mereka lebih besar dari pada anak-anak. Input juga merangsang produksi dan kompetensi bahasa pengakuisisi dimana keduanya juga merupakan prinsip akuisisi bahasa. Kata kunci: Akuisisi, Belajar, Proses Bahasa